Stability of Silver and Fluoride Contents in Silver Diamine Fluoride Solutions - Iliana Gehui Yan; Faith Miaomiao Zheng; Iris Xiaoxue Yin; Ivy Guofang Sun; Edward Chin Man Lo; Chun Hung Chu (Elsevier, 2023)
Objective: This study aims to determine the stability, alkalinity, and fluoride and silver ion concentrations of 5 commercially available 38% silver diamine fluoride (SDF) solutions-namely Advantage Arrest, e-SDF, Riva Star, Saforide, and Topamine-in 180 days. Methods: Alkalinity was determined using a pH electrode. The fluoride and silver ion concentrations were obtained using a calibrated ion-selective electrode and optical emission spectrometer, respectively. Six bottles of each product were examined on days 0 (freshly opened), 30, 60, 90, and 180. The time taken for each freshly opened product to form a black silver precipitate under room light (500 lx) and 25 °C was also recorded. Results: For 180 days, Advantage Arrest, e-SDF, Riva Star, Saforide, and Topamine had the pH range of 9.8-9.8, 10.5-10.6, 13.0-13.1, 9.8-9.8, and 9.3-9.4; fluoride ion concentration range (nearest 1000 ppm) of 40.9%-42.4%, 46.7%-50.9%, 37.0%-39.0%, 37.0%-45.7%, and 47.7%-53.4%; silver ion concentration range (nearest 1000 ppm) of 283.4-307.0, 307.3-315.4, 418.6-435.7, 266.3-281.0, and 416.2-456.1 ppm; and precipitation time (nearest hour) of 17, 12, 6, 7, and 7 hours, respectively. The percentage change of fluoride and silver could be more than 5% after 60 days. Conclusions: The alkalinity of the 5 SDF solutions remained stable after 180 days. In addition, their fluoride and silver concentrations decreased substantially after 60 days. The freshly opened SDF solutions did not precipitate within 5 hours under ambient room conditions. The alkalinity and fluoride and silver concentrations of the 38% SDF solutions could be less stable after 60 days; thereafter, the fluoride and silver concentrations decreased. Thus, the SDF solution should be used within 60 days after opening.